Carbon nanoscrolls by pyrolysis of a polymer - Yadav, Prasad; Warule, Sambhaji; Jog, Jyoti Prakash; Ogale, Satishchandra B. (Solid State Communications, 2012)
3D network of carbon nanoscrolls was synthesized starting from pyrolysis of poly(acrylic acid-co-maleic acid) sodium salt. It is a catalyst-free process where pyrolysis of polymer leads to formation of carbon form and sodium carbonate. Upon water soaking of pyrolysis product, the carbon form undergoes self-assembly to form carbon nanoscrolls. The interlayer distance between the walls of carbon nanoscroll was found to be 0.34 nm and the carbon nanoscrolls exhibited a surface area of 188 m(2)/g as measured by the BET method. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Carbon nanoscrolls; Polymer; Pyrolysis; supercapacitor

Hollow nanogold/meso-magnetite composite: pulsed laser synthesis, properties, and biosensing application - Chaudhari, Nilima; Warule, Sambhaji; Agrawal, Shailaja; Thakare, Vishal; Jouen, Samuel; Hannoyer, Beatrice; Kale, Bharat; Paknikar, Kishore; Ogale, Satishchandra B. (Journal of Nanoparticle Research, 2013)
A facile and template-free UV (Excimer) laser photolysis process is demonstrated to transform a Fe-complex into unique hollow Fe3O4 nanosphere morphology with each sphere having nanometric pores and an opening. Depending on the Fe-complex concentration and processing time interesting configurations are seen to evolve. When an identical process is applied to a mixture of Fe-complex and chloroauric acid an enthrallingly decorated Au-Fe3O4 nanostructure evolves, with Au nanoparticles surface-loaded on mesospheric Fe3O4. This room temperature process implemented under normal laboratory conditions is clearly versatile and applicable to heterojunction nanomaterials synthesis in a single-step process. The potential application of these gold-decorated magnetic nanostructures was also investigated for immuno-magnetic capture of E. coli in biosensing and these were found to be sensitive even below 1,000 cfu/ml. The test results demonstrate linear sensing response in the range of 10(3)-10(5) cfu/ml. We also show that these nanostructures can be used for simple electrical conductivity-based biosensing since they show dramatic conductivity change in a simple drop-cast test. A new laser-based approach to the synthesis of unique hollow sphere morphology of magnetite (Fe3O4) without and with Au nanoparticle decoration is presented. The potential application of these gold-decorated magnetic nanostructures was also investigated for immuno-magnetic capture of E. coli in biosensing and these were found to be sensitive even below 1,000 cfu/ml.
Keywords: E. coli cells; Fe-complex; Meso-magnetite; Nanobiotechnology; Nanocomposite; Pulse laser irradiation